Autonomia da previdência privada na relação de emprego - Ciero, Maria Teresa Leis Di (2009)
This work looks into the autonomy of the private pension system during employment relations. To that end, this study will start by describing the evolution of the social security system as from enactment of the Federal Constitution in 1988, which comprises healthcare, welfare, and public and private pension schemes. This work will then focus on inclusion of the private pension scheme into the social security system envisioned by the Federal Constitution as a mechanism for social protection. Despite the differences between the general social security regime (which is governed by law and subject to compulsory adhesion) and the private social security scheme (which is governed by private contract, optional, and based on the principle of the parties freedom to contract), both can coexist in the social security system. In conclusion, it can be seen that the purpose of the private pension system is to secure the well-being of individuals and of the community as a whole, after retirement. This work will study private pension entities and benefit plans made available by the employer to employees, showing the autonomy of social security schemes vis-à-vis employment bonds. Within this context, we will detail the reasons why the private pension plan offered by the employer (whether through an open-end or a closed-end private pension entity) cannot be confused with the benefits offered by the employer under the umbrella of the existing employment bond, whose entitlement and contribution rules are compulsorily prescribed by labor laws. As the economy stabilized in Brazil, corporate negotiations have blossomed over the last years. These developments from a positive economic scenario have translated into deep transformations in labor relations and in corporate businesses. Although the private pension alternative plays a relevant part in employment relations, it has no labor-related implications when granted by the employer, due to the parties freedom to contract as expressly warranted by the Federal Constitution. After elaborating on the legal relationship between the employer and the private pension entity, as well as that between the private pension entity and employees, during an employment bond, this work will conclude that the private pension scheme is autonomous with regard to employment relations. Although this work analyzes those plans run by open-end and closed-end private pension entities during employment relations, emphasis will be placed on plans offered by closed-end private pension entities, as these are more commonly confused with the employer status in certain circumstances, given the nature and content of their operational rules